Fabrication of an Electrochemical E. coli Biosensor in Biowells Using Bimetallic Nanoparticle‐Labelled Antibodies. Issue 2 (26th November 2014) - Eksi, Haslet; Güzel, Remziye; Güven, Burcu; Boyaci, Ismail Hakki; Solak, Ali Osman
Abstract An electrochemical biosensor was developed for the determination of Escherichia coli (E. coli) in water. For this purpose, silver‐gold core‐shell (Ag@Au) bioconjugates and anti‐E. coli modified PS‐microwells were designed in a sandwich‐type format in order to obtain higher sensitivity and selectivity. Ag@Au bimetallic nanoparticles were synthesized by co‐reduction method. The core‐shell formation was analyzed by using UV‐Vis spectroscopy and transmission electron microscopy. Biotin labeled anti‐E. coli antibodies were coupled with Ag@Au nanoparticles to form bioconjugates. The electrochemical immunosensor was prepared by immobilizing anti‐E. coli on polystyrene (PS)‐microwells via chemical bonding. These modified microwells were identified with X‐ray photoelectron spectroscopy and surface enhanced Raman spectroscopy. E. coli was sandwiched between Ag@Au bioconjugates and anti‐E. coli on PS‐microwells at different concentrations. The relationship between the E. coli concentration and stripping current of gold ions (Au3+) were investigated by square wave anodic stripping voltammetry at pencil graphite electrode. The proposed method can provide some advantages such as lower detection limit and shorter detection time. The electrochemical response for the immunosensor was linear with the concentration of the E. coli in the range of 101 and 105 cfu/mL with a limit of detection 3 cfu/mL. The procedure maintains good sensitivity and repeatability and also offers utility in the fields of environmental monitoring and clinical diagnosis.